A symmetric dual-ring cross stub based dual-band THz metamaterial absorber design for permittivity sensing applications - Alqurashi, Ahmed; Al Gburi, Ahmed Jamal Abdullah; Khanam, Sayeeda; Zafar, Esam Y.O. (Elsevier B.V., 2025)
This paper presents a novel dual-band terahertz (THz) metamaterial absorber based on a symmetric dual-ring cross-stub (SDR-CS) resonator, designed for high-sensitivity permittivity sensing. The absorber, composed of aluminum resonators and a polyamide substrate, features a compact unit cell of 80 × 80 μm with rotational symmetry. It exhibits two strong absorption peaks at 1.26 THz and 2.29 THz with near-unity absorption. Detailed electromagnetic simulations reveal the physical mechanisms underpinning the dual-band response and confirm polarization insensitivity and angular stability up to 60° incidence under TE and TM polarizations. Crucially, the device demonstrates excellent sensing performance for refractive indices in the range 1.0–3.162, achieving sensitivities of 0.148 THz/RIU (148 GHz/RIU) and 0.28 THz/RIU (280 GHz/RIU) at the lower and higher resonance frequencies, respectively. The quality factors (Q) are 32.3 and 39.3, resulting in figure-of-merits (FOM) of 39.3 and 32.3 RIU–1, outperforming many reported metamaterial sensors with larger sizes or more complex materials. These attributes underscore the absorber’s potential as a compact, efficient, and highly sensitive platform for THz permittivity sensing with applications in biomedical diagnostics, chemical identification, and environmental monitoring.